Structural Elucidation and Toxicity Evaluation of Bioactive Compounds from the Leaves and Stem woods of Synadenium glaucescens Pax. - Credo, David; Mabiki, Faith Philemon; Machumi, Francis; Cornett, Claus (UI Scholars Hub, 2022)
The leaves and stem woods of Synadenium glaucescens Pax. are traditionally used for treatment of various human diseases in Tanzania. However, there is limited information on the structural elucidation and toxicity properties of bioactive compounds responsible for their pharmacological properties. Thus, this study was aimed to elucidate and evaluate toxicity properties of bioactive compounds from these parts. Separation of bioactive compounds was achieved by using column chromatographic method, whereas their structures were determined by GC-MS and NMR data and by comparing with literature spectroscopic data. Toxicity properties of isolated compounds was done by brine shrimp lethality test (BSLT) method. In this study, column chromatographic separation led to isolation of tetracosane (1), hexadecyl palmitate (2), octacosane (3), tetracosanol (4) and β-sitosterol (5) from the leaves and 1-hexacosene (6), campesterol (7), octadecanoic acid (8) and tetracosanoic acid (9) from the stem woods. BSLT of compounds isolated in sufficient amount (1, 2, 3, 4, 5 and 7) were revealed to be non-toxic to brine shrimp larvae (LC50 >100 µg/ml). Except compound 5, this study reports the isolation of other eight (8) compounds for the first time from this plant. Therefore, it can be reasonably concluded that S. glaucescens is a good source of bioactive compounds which justify its traditional uses in treatment of various ailments. Additionally, observed non-toxic effect of the tested compounds indicates safety and it is expected that its traditional use has no toxicity effect.